Binary Image Object Identification Using Fuzzy Logic and Labeling Breadh-First - Anita Sindar RM Sinaga (Journal of Telematics and Informatics, 2018)
The colors are derived from the results of eyes responded the reflected rays of the color of the object. Fuzzy logic that is to determine a color area along with the degree of its membership. The image can be identified from the dominant color, with the image of the binary value of 1 is stated in black and white were declared a value of 0. Each of the pixels that make up the image are mapped into the staple color and then converted into a binary image, the white, black and gray colors obtained from I (Intensity=0) and S (Saturation=1) while Hue is predominantly Red. Binary image shows a number of objects, based on the colors black and white, to find out the number of objects used labeling objects. The use of colors based on the Intensity Hue Saturation colors attribute aims to more easily identify the color of black and white objects. Labeling is a process of granting the same label on a bunch of pixels forming the object to each other on one image, Breadh-first is the practical object labeling technique provides the best results compared to the method of inundation (flood filling) other. This research attempts to identify objects that have the same invisible dominant color.Keywords: Dominant Color, Binary Image, Fuzzy Logic, Labeling